Grandisin and its therapeutic potential and pharmacological activities: A review - Dinesh Kumar Patel (Elsevier, 2022)
Plant derived products and phytoconstituents have been used in medicine for the treatment of human disorders and associated secondary complication since a very early age. Phytoconstituents have numerous biological potential and therapeutic benefits in medicine. Lignans are a kind of non-flavonoids polyphenols which can bind to the estrogen receptors and function as phytoestrogens. Lignans have anti-tumor, antioxidant, and other pharmacological activities. Scientific data of grandisin have been collected from different databases in the present work and analyzed in order to know the biological importance and therapeutic benefit of grandisin in medicine. Scientific data have been collected from Science Direct, Google, Google Scholar, PubMed, and Scopus using term herbal medicines, traditional Chinese medicine, lignans, and grandisin. Detailed pharmacological activities of grandisin have been analyzed in the present investigation through scientific data analysis of different scientific research work. However, analytical data of grandisin have been also collected and analyzed in the present investigation. Grandisin is an important class of tetrahydrofuran neolignan found to be present in Virola surinamensis, and Piper solmsianum. Grandisin have high trypanocidal activity against the tripomastigote forms of Trypanosoma cruzi. Scientific study signified the biological potential of grandisin in medicine for their anti-leishmanial, chemoprotective, cytotoxicity, anti-angiogenic, anti-nociceptive, anti-inflammatory, and larvicidal activity. However, it's potential for vascular diseases, biotransformation and metabolism have been also discussed in the present work. Analytical data revealed the importance of various analytical techniques for the separation, isolation and identification of grandisin from various medicinal plants, including Aglaia leptantha, and Cryptocarya crassinervia.